Revisiting Nnamdi Azikiwe’s Idea on Ethnicity and the Implication for Nation-Building in Nigeria - Osemwengie, Ikonnaya Okomba (NIU Journal of Social Sciences, 2026)
Nigeria continues to grapple with national integration, political instability, and calls for restructuring, often attributed to the country’s complex ethnic landscape. This paper revisits Nnamdi Azikiwe’s perspectives on ethnicity and assesses their relevance for nation-building in present-day Nigeria. Contrary to the view that ethnic diversity is inherently problematic, the study contends that the challenge lies in the political manipulation of ethnic identities. Drawing on Azikiwe’s speeches and writings, the paper examines his belief that ethnicity is a natural social reality that can be positively managed through constitutionalism, inclusive governance, federalism, and the protection of fundamental rights. Employing a qualitative and historical methodology, the analysis situates Azikiwe’s thought within Nigeria’s postcolonial experience and current political dynamics. The findings suggest that Azikiwe regarded ethnicity not as a barrier to national unity, but as a potential resource for promoting stability and cohesion, provided it is addressed with justice, equitable development, and democratic leadership. The paper concludes that Azikiwe’s ideas offer valuable insights for advancing national integration and fostering sustainable nation-building in Nigeria today. Keywords: Nnamdi Azikiwe, Ethnicity, Nation-Building, National Integration, Federalism